ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PENDIDIKAN DI PROVINSI JAWA TENGAH TAHUN 2015-2021 - Rahayu, Vita Dwi; Afriza, Edi Fitriana; Aisyah, Iis (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
This research is motivated by the low education index of Central Java province among the six provinces on the island of Java. The low education index is influenced by several factors, and it is essential to identify which factors are dominant in influencing the education index. The purpose of this study was to analyze the effect of School Participation Rate (APS), Average Years of Schooling (RLS), and the education budget on the education index in Central Java. The population and sample of this study are the Education Index, School Participation Rate, Average Years of Schooling, and the APBD for Education in Central Java from 2015 to 2021. This research uses descriptive quantitative methods. Data in the form of time series were collected through literature study techniques and visiting the official website of the Central Statistics Agency (BPS). The independent variables in this study are the School Participation Rate, Average Years of Schooling, and APBD in the education sector, while the dependent variable is the education index. Hypotheses were tested using multiple linear regression analysis. The results showed that the School Participation Rate has a significant effect on the education index with a significance value of 0.016. The Average Years of Schooling also has a significant effect on the education index with a significance value of 0.000. Additionally, the education budget shows an effect on the education index with a significance value of 0.024.